Intelligence in childhood and atherosclerosis of the carotid and peripheral arteries in later life: the Lothian Birth Cohort 1936. - Catharine R Gale; Elizabeth Eadie; Avril Thomas; Mark E Bastin; John M Starr; Joanna Wardlaw; Ian J Deary (PLoS ONE)
Objective There is some evidence that people who score higher on tests of intelligence in childhood have lower carotid intima-media thickness and higher ankle brachial index in middle age. These findings need replicating in other, older populations. We investigated the prospective relationship between intelligence in childhood and atherosclerosis in the carotid and peripheral arteries at age 73 years. Methods Participants were 713 members of the Lothian Birth Cohort 1936 whose intelligence was assessed at age 11 years. At age 73 years, carotid intima-media thickness and degree of stenosis were measured using ultrasound imaging; ankle-brachial index was measured using Doppler ultrasound. Results There were no significant associations between intelligence at age 11 and measures of atherosclerosis at age 73. In age- and sex-adjusted analyses, for a standard deviation higher score in intelligence, intima-media thickness (x 10) was lower by 0.07 (-0.20, 0.06) mm and ankle brachial index (x 10) was lower by 0.09 (-0.24, 0.07); odds ratios for having carotid stenosis >25% or peripheral arterial disease were 0.98 (0.82, 1.16) and 1.05 (0.81, 1.36) respectively. Conclusion In this study of people aged 73 years, higher childhood intelligence was not associated with reduced risk of atherosclerosis in the carotid or peripheral arteries.